Manajemen dan Kepemimpinan Kelembagaan Organisasi UMKM di Kabupaten Kuningan - Donni Juni Priansa; Ganjar Mohamad Disastra (LPPM Politeknik Piksi Ganesha, 2025)
MSMEs in Kuningan Regency have great potential to develop. However, institutional management and leadership in MSME organizations in Kuningan Regency are still not optimal. The problems identified include weak organizational structures, the absence of an organized management system, the absence of a clear division of tasks, and the lack of a structured business plan. In addition, MSME leadership tends to be operational and has not been able to respond to long-term strategic challenges. This community service was carried out on July 3-4, 2025 by involving the target community as participants. The results of the activity showed a positive response from the community, with the hope of program sustainability on more diverse themes. This finding emphasizes the importance of strengthening institutional management and leadership as the key to MSME development.